Cognitive determinants of health information seeking behavior through social media platforms among Malaysian adults - Khairul Amin, Khairul Hafidz Alkhair; Mohd Nazan, Ahmad Iqmer Nashriq (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Health information-seeking behaviour is a process of gathering information for individuals to understand and cope with his/her health problems. Apart from the Internet or Web 1.0, Web 2.0 tools has been increasingly used as alternative to seek health information and one such tool is social media platform. This study aims to identify cognitive determinants of health information-seeking behaviour through social media platforms among Malaysian adults. Methods: A cross-sectional study by means of convenience sampling was conducted during a nationwide pandemic lockdown. Cognitive determinants were defined as respondent’s perceived usefulness, perceived ease of user, perceived benefit, perceived costs, perceived behavioural control, and perceived risk towards social media use. Questionnaires were distributed via Google Form link to multiple social media platforms and cross-platform messaging app. Differences between group of sociodemographic factors and other independent variables were tested with nonparametric tests while multiple linear regression was employed to determine the significant predictors of the health information seeking behavior. Results: A total of 705 individuals responded to the survey invitation, the majority of which were females (65%), Malay (93.6%), married (52.1%), and received tertiary education (88.5%). Multiple linear regression analysis showed that perceived benefit (β= 0.612, 95% CI: 0.517-0.708, p<0.001), perceived usefulness (β= 0.653, 95% CI: 0.453-0.853, p<0.001), and perceived risk (β= 0.131, 95% CI: 0.03-0.259, p=0.044) significantly predict health information seeking behavior through social media platform. Conclusion: Our findings provide fundamental grounds for stakeholders to better understand and influence online behavior. Staying abreast of the current online trend is crucial as more people have begun to rely on social media for health information.